For a certain integer n , 2 2 0 0 − 3 1 × 2 1 9 2 + 2 n is a perfect square. What is n ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The "before last" step is simply to figure out the value of p , q in the pythagorean triplet ( 1 5 , p , q ) by casework which comes out to be p = 8 , q = 1 7 thus giving us the value of n = 1 9 8 when we compare with the given expression.
We note that:
2 2 0 0 − 3 1 ˙ 2 1 9 2 = ( 2 8 − 3 1 ) ˙ 2 1 9 2 = ( 2 5 6 − 3 1 ) ˙ 2 1 9 2
= 2 2 5 ˙ 2 1 9 2 = 1 5 2 ˙ 2 1 9 2
Now consider the perfect square:
(15+x)^2\dot{} 2^{192} = (15^2+30x+x^2)\dot{} 2^{192} = 15^\dot{} 2^ {192} + (30x+x^2)\dot{} 2^{192}
= 2 2 0 0 − 3 1 ˙ 2 1 9 2 + ( 3 0 x + x 2 ) ˙ 2 1 9 2
For 2 2 0 0 − 3 1 ˙ 2 1 9 2 + 2 n to be a perfect square, we equate
( 3 0 x + x 2 ) ˙ 2 1 9 2 = 2 n
and find that it is true when x = 2 then we have:
( 6 0 + 4 ) ˙ 2 1 9 2 = 6 4 ˙ 2 1 9 2 = 2 6 ˙ 2 1 9 2 = 2 1 9 8 = 2 n ⇒ n = 1 9 8
Problem Loading...
Note Loading...
Set Loading...
2 2 0 0 − ( 2 5 − 1 ) 2 1 9 2 + 2 n
= 2 2 0 0 − 2 1 9 7 + 2 1 9 2 + 2 n
= 2 1 9 2 ( 2 5 6 − 3 2 + 1 + 2 n − 1 9 2 )
= 2 1 9 2 ( 2 2 5 + 2 n − 1 9 2 )
Now, 2 2 5 + 2 6 = 2 2 5 + 6 4 = 2 8 9 = 1 7 2
Hence, n − 1 9 2 = 6
n = 1 9 8